Celularidade do leite e Unidades Formadoras de Colônias nas mastites causadas por Staphylococcus coagulase positiva e coagulase negativa - Langoni, Helio [UNESP]; Guimarães, Felipe Freitas [UNESP]; da Costa, Elizabeth Oliveira; Joaquim, Samea Fernandes [UNESP]; Menozzi, Benedito Donizete [UNESP] (FapUNIFESP (SciELO), 2015)
Mastitis is the main affection of cattle intended for dairy production, which significantly impacts the milk production chain, with consequences yet to public health. It was studied aspects related to etiology, cellularity and bacterial count in 10 dairy farms, in the State of São Paulo. There were examined 1148 milking cows, totaling 4584 mammary glands. Cases in which there was isolation coagulase positive staphylococci (CPS) and coagulase-negative staphylococci (CNS) were considered. The results showed microbiota with various different pathogens and CNS (128 cases) and CPS (45), Staphylococcus aureus (90), Streptococcus agalactiae (70), Streptococcus dysgalactiae (69), Streptococcus uberis (29), Corynebacterium spp . (230), Klebsiella pneumoniae (28), Klebsiella oxytoca (2), Escherichia coli (15), Enterobacter spp. (3). The somatic cell count (SCC) related to CPS and CNS showed no differences among the evaluated properties, although with significant differences when evaluating the SCC between both groups of staphylococci, as evidenced by comparing discreet CNS and exuberant CPS (P < 0.01), discreet CPS and exuberant CPS (P < 0.001) and moderate SCN and exuberant SCP (P < 0.01). The evaluation of SCC was related to the intensity of infection, considering how slight growth isolation of up to nine colonies, moderate ten to 29 colonies and lush, with 30 or more colonies, revealed for both groups of staphylococci that the higher the number of colony forming units (CFU), SCC is higher being larger in cases of CPS. The results indicate that the importance of both CPS and CNS when considering the high occurrence of the evaluated properties and the fact that it raises the SCC, which compromises the quality of milk. We conclude that when there is a larger number of CFU, is concomitantly higher SCC/ml of milk, in the case of CPS and CNS, which shows a direct relationship of the intensity of the infectious process with the response of milk cellularity, as well as the relevance of these in the etiology of mastitis and negatives aspects to both the production and the quality of milk produced in properties.
Milk cellularity and colony forming units in mastitis caused by coagulase-positive staphylococci and coagulase negative
Keywords: Cellularity; Colony forming units; Milk quality; Staphylococci